Analisis Sarkasme pada Kolom Komentar di Akun Instagram Belinda.Mci11 - Widia Sari; Rani Ardesi Pratiwi; Maulidawati Maulidawati (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study is titled “Analysis of Sarcasm Languages on Comment Column in Belinda Instagram Account Belinda.mci11”. The purpose of this study is to describe the form of sarcasm language in the comments column on the Belinda.mci11 Instagram account. The data in this study is a comment sentence containing sarcasm style on the Instagram account Belinda.mci11. The source of this research data is a comment column on the post of Belinda.mci11 Instagram account posted on November 27, 2023. The data collection technique in this study uses two techniques, namely documentation and reading-record techniques. The results of this study showed that the discovery of the form of sarcasm in the comments column on the Belinda.mci11 account consists of 9 propositional sarcasm data, 27 lexical sarcasm data, 45 ‘like’- prefixed sarcasm data, and 3 illocutionary sarcasm data.